2017
DOI: 10.1186/s12889-017-4594-z
|View full text |Cite|
|
Sign up to set email alerts
|

Parents’ and caregivers’ experiences and behaviours when eating out with children with a food hypersensitivity

Abstract: BackgroundFor parents and caregivers of food hypersensitive (FH) children, accommodating their child’s dietary needs when eating out can be a challenging experience. This study explored caregivers’ experiences and behaviours when eating out with their FH child in order to gain insights into how they support and prepare their child in negotiating safe eating out experiences.MethodsA cross-sectional, qualitative design was used. In depth, semi-structured interviews were carried out with 15 caregivers of children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 28 publications
1
61
0
3
Order By: Relevance
“…As an inherently social experience, a number of pre legislation studies have reported the embarrassment and alienation experienced by customers with food allergy when eating outside the home, and these experiences led some consumers to take undue risks or limit their social activities as a result. 6,[13][14][15][16][17] The rise in awareness noted by participants suggested a degree of normalization of food allergy which was welcomed by many.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As an inherently social experience, a number of pre legislation studies have reported the embarrassment and alienation experienced by customers with food allergy when eating outside the home, and these experiences led some consumers to take undue risks or limit their social activities as a result. 6,[13][14][15][16][17] The rise in awareness noted by participants suggested a degree of normalization of food allergy which was welcomed by many.…”
Section: Discussionmentioning
confidence: 98%
“…Implicit within these improvements was a perception of raised food allergy awareness on the part of eating out venues and their staff, particularly in relation to the importance of allergen avoidance for customers with food allergy. As an inherently social experience, a number of pre legislation studies have reported the embarrassment and alienation experienced by customers with food allergy when eating outside the home, and these experiences led some consumers to take undue risks or limit their social activities as a result . The rise in awareness noted by participants suggested a degree of normalization of food allergy which was welcomed by many.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 summarizes the study characteristics. Most of the studies were conducted in Europe (the UK, Finland, Sweden and Denmark) (Akeson et al, 2007;Alanne et al, 2014;Alanne, Laitinen, Söderlund, & Paavilainen, 2012;Begen et al, 2018;Gallagher et al, 2012;Gunnarsson & Hydén, 2009;Lagercrantz et al, 2017;MacKenzie et al, 2015;Pitchforth et al, 2011;Rouf et al, 2012;Stjerna et al, 2014;Valentine & Knibb, 2011), some from the Americas (the US, Canada and Brazil) (Abdurrahman et al, 2013;Broome et al, 2015;Franciosi et al, 2012;Gillespie et al, 2007;Gupta et al, 2008;Harrington et al, 2015;Vargas et al, 2011;Yonamine et al, 2013) and two studies were conducted in Australia and New Zealand (Crowley et al, 2012;McBride et al, 2010). Several studies had mixed study populations and included parents and children across different age groups, see Table 2.…”
Section: Search Outcomementioning
confidence: 99%
“…The others described a deductive or inductive qualitative approach using a content or thematic analysis. The data program, NVivo, was used in the analysis of the data in some studies (Abdurrahman et al, 2013;Akeson et al, 2007;Begen et al, 2018;Crowley et al, 2012;Dean et al, 2016;Gallagher et al, 2012;Gupta et al, 2008;. The data were collected using individual interviews, focus group interviews and mixed methods such as interviews, diaries and photographs, see Table 2.…”
Section: Search Outcomementioning
confidence: 99%
“…Living with food hypersensitivities involves constant risk assessments surrounding the foods one consumes. This is especially the case when eating outside the home [4,[6][7][8]. Those with food intolerance wish to avoid repeatable adverse reactions to foods such as bloating, constipation, vomiting and diarrhoea.…”
Section: Food Hypersensitivitymentioning
confidence: 99%